Applications of MOFs and Their Derivatives in Lithium–Oxygen Battery Cathodes: Development and Challenges - Haitao Ma; Shaohua Luo; Jun Cong; Shengxue Yan (Inorganics)
Lithium–oxygen batteries have attracted considerable attention in recent years due to their high energy density and potential applications. However, the slow kinetics of the cathode reaction and the unstable products in lithium–oxygen batteries have limited their practical applications. Metal–organic frameworks (MOFs) and their derivatives have emerged as a novel class of functional materials, thus becoming ideal candidates for the cathode of lithium–oxygen batteries. This is due to their high specific surface area, structural tunability, and abundant active sites. This paper presents a review of the research progress made in the field of MOFs and their derivatives in the cathode of lithium–oxygen batteries. It provides a summary of the design and synthesis strategies employed in the development of MOF-based catalysts, with a particular focus on the application of primary MOFs materials, MOF-derived materials and MOF composite materials in Li-O2 batteries. Additionally, it analyses the catalytic mechanism of MOFs and their derivatives in the ORR/OER. The comprehensive analysis demonstrates that MOFs and their derivatives are ideal candidates for the cathodes of lithium–oxygen batteries due to their high specific surface area, structural tunability, and abundant active sites. However, the electrical conductivity of MOFs is usually low and needs to be enhanced by composites or derivative materials. This paper reviews the research progress on MOFs and their derivatives in lithium–oxygen battery cathodes, focuses on the design and synthesis strategies of MOF-based catalysts, and discusses their catalytic mechanisms in the ORR/OER.